Application of B cell immortalization for the isolation of antibodies and B cell clones from vaccine and infection settings - Boswell, Kristin L.; Watkins, Timothy A.; Cale, Evan M.; Samsel, Jakob; Andrews, Sarah F.; Ambrozak, David R.; Driscoll, Jefferson I.; Messina, Michael A.; Narpala, Sandeep; Hopp, Christine S.; Cagigi, Alberto; Casazza, Joseph P.; et al. (Frontiers in Immunology, 2022)
The isolation and characterization of neutralizing antibodies from infection and vaccine settings informs future vaccine design, and methodologies that streamline the isolation of antibodies and the generation of B cell clones are of great interest. Retroviral transduction to express Bcl-6 and Bcl-xL and transform primary B cells has been shown to promote long-term B cell survival and antibody secretion in vitro, and can be used to isolate antibodies from memory B cells. However, application of this methodology to B cell subsets from different tissues and B cells from chronically infected individuals has not been well characterized. Here, we characterize Bcl-6/Bcl-xL B cell immortalization across multiple tissue types and B cell subsets in healthy and HIV-1 infected individuals, as well as individuals recovering from malaria. In healthy individuals, naïve and memory B cell subsets from PBMCs and tonsil tissue transformed with similar efficiencies, and displayed similar characteristics with respect to their longevity and immunoglobulin secretion. In HIV-1-viremic individuals or in individuals with recent malaria infections, the exhausted CD27-CD21- memory B cells transformed with lower efficiency, but the transformed B cells expanded and secreted IgG with similar efficiency. Importantly, we show that this methodology can be used to isolate broadly neutralizing antibodies from HIV-infected individuals. Overall, we demonstrate that Bcl-6/Bcl-xL B cell immortalization can be used to isolate antibodies and generate B cell clones from different B cell populations, albeit with varying efficiencies.